1993
DOI: 10.3102/01623737015002195
|View full text |Cite
|
Sign up to set email alerts
|

Data Analysis Strategies for Mixed-Method Evaluation Designs

Abstract: Four integrative data analysis strategies for mixed-method evaluation designs are derived from and illustrated by empirical practice: data transformation, typology development, extreme case analysis, and data consolidation/merging. The appropriateness of these strategies for different kinds of mixed-method intents is then discussed. Where appropriate, such integrative strategies are encouraged as ways to realize the full potential of mixed-methodological approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
234
0
9

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 367 publications
(244 citation statements)
references
References 16 publications
1
234
0
9
Order By: Relevance
“…Qualitative and quantitative methods were used to collect data during Round 1 and 2. During each interpretation phase, the data was blended to compare and confirm results (Caracelli & Greene, 1993;Sandelowski, 2000). Although consensus is typically conceptualized and represented numerically, consensus can also be assessed by comparing and interpreting qualitative data (Sandelowski, 2000).…”
Section: Mixed Methodsmentioning
confidence: 99%
“…Qualitative and quantitative methods were used to collect data during Round 1 and 2. During each interpretation phase, the data was blended to compare and confirm results (Caracelli & Greene, 1993;Sandelowski, 2000). Although consensus is typically conceptualized and represented numerically, consensus can also be assessed by comparing and interpreting qualitative data (Sandelowski, 2000).…”
Section: Mixed Methodsmentioning
confidence: 99%
“…The categorization followed an iterative process through which typologies of well-being components were developed after data collection in each village (Caracelli and Greene 1993). Data entry captured the entirety of the interview scripts, giving the team an overview of all the data.…”
Section: Qualitative Analysismentioning
confidence: 99%
“…Nunnally (1978) suggested that a set of items with a coefficient alpha greater than 0.7 is considered internally consistent. Within the context of this study, typology development has been used as analytical strategy where a quantitative survey was conducted, developed factors through a factor analysis and using this factors as a typology (Caracelli and Greene, 1993). Items of Commercialization Activities of Research Results are regrouped into different groups based on the extraction value of the rotated component matrix namely CNB, TT and IPAW as indicated in Table 3.…”
Section: Frequency Analysis Of Commercialization Activities Of Researmentioning
confidence: 99%